hnRNP F Influences Binding of a 64-Kilodalton Subunit of Cleavage Stimulation Factor to mRNA Precursors in Mouse B Cells - Veraldi, Kristen L. (American Society for Microbiology, 2001)
Previous studies on the regulation of polyadenylation of the immunoglobulin (Ig) heavy-chain pre-mRNA argued for trans-acting modifiers of the cleavage-polyadenylation reaction operating differentially during B-cell developmental stages. Using four complementary approaches, we demonstrate that a change in the level of hnRNP F is an important determinant in the regulated use of alternative polyadenylation sites between memory and plasma stage B cells. First, by Western analyses of cellular proteins, the ratio of hnRNP F to H or H′ was found to be higher in memory B cells than in plasma cells. In memory B cells the activity of CstF-64 binding to pre-mRNA, but not its amount, was reduced. Second, examination of the complexes formed on input pre-mRNA in nuclear extracts revealed large assemblages containing hnRNP H, H′, and F but deficient in CstF-64 in memory B-cell extracts but not in plasma cells. Formation of these large complexes is dependent on the region downstream of the AAUAAA in pre-mRNA, suggesting that CstF-64 and the hnRNPs compete for a similar region. Third, using a recombinant protein we showed that hnRNP F could bind to the region downstream of a poly(A) site, block CstF-64 association with RNA, and inhibit the cleavage reaction. Fourth, overexpression of recombinant hnRNP F in plasma cells resulted in a decrease in the endogenous Ig heavy-chain mRNA secretory form-to-membrane ratio. These results demonstrate that mammalian hnRNP F can act as a negative regulator in the pre-mRNA cleavage reaction and that increased expression of F in memory B cells contributes to the suppression of the Ig heavy-chain secretory poly(A) site.